Extended follow-up of a phase 3 trial in relapsed multiple myeloma: final time-to-event results of the APEX trial - Richardson, Paul G.; Sonneveld, Pieter; Schuster, Michael; Irwin, David; Stadtmauer, Edward; Facon, Thierry; Harousseau, Jean-Luc; Ben-Yehuda, Dina; Lonial, Sagar; Goldschmidt, Hartmut; Reece, Donna; Miguel, Jesus San; et al. (Blood, 2007)
Initial analysis of the Assessment of Proteasome Inhibition for Extending Remissions (APEX) trial of relapsed multiple myeloma patients showed significantly longer time to progression, higher response rate, and improved survival with single-agent bortezomib versus high-dose dexamethasone. In this updated analysis (median follow-up: 22 months), survival was assessed in both arms, and efficacy updated for the bortezomib arm. Median survival was 29.8 months for bortezomib versus 23.7 months for dexamethasone, a 6-month benefit, despite substantial crossover from dexamethasone to bortezomib. Overall and complete response rates with bortezomib were 43% and 9%, respectively; among responding patients, 56% improved response with longer therapy beyond initial response, leading to continued improvement in overall quality of response. Higher response quality (100% M-protein reduction) was associated with longer response duration; response duration was not associated with time to response. These data confirm the activity of bortezomib and support extended treatment in relapsed multiple myeloma patients tolerating therapy. This study is registered at http://clinicaltrials.gov (Study ID NCT00048230).
Gesehen am 21.01.2022